Politično življenje izginulih - Kralj, Gašper (Časopis za kritiko znanosti, 2005)
The political life of the disappeared: narratives of rebellion in Guatemala. This article opens with contextualization of Guatemala and then proceeds with an ethnographical reflection from an abandoned plantation from the east of the country. This serves as an example as how to think power in extreme forms of the neoliberal offensive of capital. The second part of the article then focuses on possible ways out, primarly upon the aestetic-political practices of the relatives of the dissapeared (desaparecidos) during the long standing military conflict in the country. A case study concerns HIJOS as a meeting place where the children of the disappeared have unified their personal histories into a narrative of a whole generation of social rebels. Through this they gradually trasformed themselves into collective able of political life, the public reading of reality and thinking the world in terms of their own image.
Keywords: dissappeard; izginuli; naracija upora; social anthropology; nova družbena gibanja; narratives of rebellion; Latin America; socialna antropologija; Latinska Amerika; new social movements; HIJOS; Gvatemala; Guatemala